Environmental Cues: A Methodology for Studying Meaning in Built Environment - TOSUN, VEHBİ (Deniz Yengin, 2019)
The interest in culture and built environment relations has received a growing attention during the last decades. The culture and built environment relations are more crucial when changes in both are more rapid and excessive since such changes can severely threaten continuity in the built environment and culture and may have undesirable physical, social and culturel consequences. Environmental cues which communicate meanings at different levels are very helpful in studying culture and built environment relations as well as changes in both them across different areas and over time. Than the task is, how one can study what they communicate, how they communicate, which are the most important ones, how one can analyze those cues and what meanings they communicate to the local and other people. In this paper the theoretical framework as well as the model for analyzing changes in culture and the built environment is established. Research methods and the procedures are discussed in detail and a comprehensive research methodology for analyzing the culture and built environment relations via environmental cues is proposed. The proposed approach can be used for different environments, at different scales as well as in incorporating the values, meanings and lifestyles of the different user groups, in designing the new.

Son yıllarda kültür ve yapılandırılmış çevre ilişkilerine artan bir ilginin olduğu görülmektedir. Kültür ve yapılandırılmış çevre ilişkileri, değişimlerin daha hızlı ve aşırı olduğu durumlarda daha da önem kazanır, çünkü bu değişimler yapılandırılmış çevrenin ve kültürün sürekliliğini ciddi bir şekilde tehdit edebilir ve istenmeyen fiziksel, sosyal ve kültürel sonuçlara yol açabilir. Farklı seviyelerde anlamları ifade eden ve ileten çevresel ipuçları, kültür ve yapılandırılmış çevre ilişkilerinin yanı sıra her ikisinde de farklı yerlerdeki ve zaman içindeki değişikliklerin incelenmesinde çok yararlıdır. Bu noktada hedef, çevresel ipuclarının ne ilettiklerini, nasıl ilettiklerini, en önemlilerinin hangileri olduğunu, bu ipuçlarının nasıl analiz edilebileceği, yerel ve diğer gruplar için ne anlama geldiklerini anlamaktır. Bu yazıda teorik bir çerçeve çizilerek, kültür ve yapılandırılmış çevredeki değişimleri analiz edebilmek için bir model oluşturulmuştur. Bu amaçla, araştırma yöntemleri ve prosedürleri ayrıntılı olarak ele alınmış, kültür ve yapılandırılmış çevre ilişkilerinin çevre ipuçlarıyla analiz edilmesi için kapsamlı bir araştırma metodolojisi önerilmiştir. Önerilen yaklaşım, farklı ortamlarda, farklı ölçeklerde uygulanabilirken, farklı kullanıcı gruplarının değerlerinin, anlamlarının ve yaşam tarzlarının, yeni tasarımlarda yansıtılmasında yararlı olacaktır.
Çevresel İpuçları: Yapı Çevresinin Anlamının İncelenmesi İçin Bir Yöntem
Keywords: Built Environment; Culture; Meaning; Environmental Cues; Methodology